Proteasome subunit PSMC3 variants cause neurosensory syndrome combining deafness and cataract due to proteotoxic stress. Issue 7 (5th June 2020) - Kröll‐Hermi, Ariane; Ebstein, Frédéric; Stoetzel, Corinne; Geoffroy, Véronique; Schaefer, Elise; Scheidecker, Sophie; Bär, Séverine; Takamiya, Masanari; Kawakami, Koichi; Zieba, Barbara A; Studer, Fouzia; Pelletier, Valerie; et al.
Abstract: The ubiquitin–proteasome system degrades ubiquitin‐modified proteins to maintain protein homeostasis and to control signalling. Whole‐genome sequencing of patients with severe deafness and early‐onset cataracts as part of a neurological, sensorial and cutaneous novel syndrome identified a unique deep intronic homozygous variant in the PSMC3 gene, encoding the proteasome ATPase subunit Rpt5, which lead to the transcription of a cryptic exon. The proteasome content and activity in patient's fibroblasts was however unaffected. Nevertheless, patient's cells exhibited impaired protein homeostasis characterized by accumulation of ubiquitinated proteins suggesting severe proteotoxic stress. Indeed, the TCF11/Nrf1 transcriptional pathway allowing proteasome recovery after proteasome inhibition is permanently activated in the patient's fibroblasts. Upon chemical proteasome inhibition, this pathway was however impaired in patient's cells, which were unable to compensate for proteotoxic stress although a higher proteasome content and activity. Zebrafish modelling for knockout in PSMC3 remarkably reproduced the human phenotype with inner ear development anomalies as well as cataracts, suggesting that Rpt5 plays a major role in inner ear, lens and central nervous system development. Synopsis: Whole genome sequencing in a large consanguineous family with neurosensory syndrome revealed a unique homozygous deep intronic pathogenic variant in PSMC3, encoding one of the proteasome subunit. Further in vitro and in vivo analyses confirmed the pathogenicity of the PSMC3 mutation. This is the first implication of a 26S proteasome AAA‐ATPase of the 19S proteasome regulatory complex in a neurosensorial disease with early onset cataract and deafness. Functional analysis using patient's cells revealed a pathogenic mechanism with proteasome impairment resulting in proteotoxic stress with over‐activation of the TCF11/Nrf1 transcriptional pathway. Zebrafish model reproduces the human phenotype with cataract and ear malformations. PSMC3 plays a major role in inner ear, lens and central nervous system development. These results expand our knowledge on the genetic background of the emerging proteasomopathy. Abstract : Whole genome sequencing in a large consanguineous family with neurosensory syndrome revealed a unique homozygous deep intronic pathogenic variant in PSMC3, encoding one of the proteasome subunit. Further in vitro and in vivo analyses confirmed the pathogenicity of the PSMC3 mutation.